Digital Student Identity Systems and Sustainable Governance in Higher Education: An Empirical Study Using the Technology Acceptance Model - Hajdenkumer, Andraž; Sternad Zabukovšek, Simona (Sustainable Governance in the Age of Artificial Intelligence: Interdisciplinary Perspectives on ESG, Digital Transformation and Corporate Responsibility, 2026)
Digital identity systems are becoming an important component of higher education institutions' digital transformation, enabling more efficient administrative processes and improved access to campus services. This study examines students’ acceptance of digital student identification cards using the Technology Acceptance Model (TAM). An extended TAM framework incorporating trust in system security was applied to analyse the relationships between perceived usefulness, perceived ease of use, attitude toward use, behavioural intention, and trust. Empirical data were collected through a survey of students enrolled at three Slovenian universities. Factor analysis revealed that perceived usefulness consists of two dimensions: administrative functions and student services. Regression analysis showed that perceived ease of use and the perceived usefulness of administrative functions significantly influence students’ attitudes toward digital student identification cards. Trust in system security also positively affects the perceived usefulness of administrative functions. The study contributes to understanding the role of digital identity systems within the digital transformation of higher education institutions.